Analisis Pengaruh Capital Adequacy Ratio (CAR), Financing Deposit to Ratio (FDR), Biaya Operasional dan Pendapatan Operasional (BOPO) terhadap Profitabilitas - Yeni Eva Damayanti; Afan Fanani; Nailatul Khoiriyah (Jurnal Bisnis Islam dan Kewirausahaan, 2023)
This study aims to determine and analyze the effect of Capital Adequacy Ratio (CAR), Financing Deposit to Ratio (FDR), Operating Costs and Operating Income (BOPO) on profitability at BRI Syariah banks. To achieve these objectives, this research uses quantitative research using secondary data from IDX. Multiple linear regression as an analytical tool. The data obtained shows that it is valid and reliable. The results showed that the CAR and BOPO variables partially had a negative and significant effect on the ROE variable, while the FDR variable had a negative and insignificant effect on the ROE variable. Suggestions for research partners to increase profitability need to pay attention to the influence of the level of risk of financing (BOPO). And suggestions for future researchers to be able to add or use other variables not examined in this study and can also add samples, this aims to increase the accuracy of the data